Load Balancing Algorithm for Supply Chain of Processed Oil Distribution - Suryani Wan Awang, Wan; Aezwani Wan Abu Bakar, Wan; Nur Syuhaida Wan Zulkifli, Wan; Man, Mustafa (International Journal of Engineering and Technology, 2018)
This study focuses on downstream stage that comprises of oil refinery and distribution. The distribution of oil via supply chain is developed using load balancing method to determine how much oil is needed to distribute to factory and gas station in a particular area. This method will not only ensure the stability of the petroleum products distribution system to meet the customer demand but also considers other factors such as population in that particular area. Current practice is where the distribution of processed oil is based on customer order. Hence, customers refer to the factories and gas stations. The distribution issues arise when there’s a delay to the processed oil delivery and also uncontrollable of supply chain. This scenario results in not meeting customer order due to imbalance of processed oil distribution because of uncontrolled distribution order. Therefore, this paper proposes a load balancing algorithm to be applied in supply chain of processed oil distribution. The objective is to supply processed oil to the customers according to the right distribution order. As a result, processed oil distribution can be managed in a more systematic way to meet the demand of the end customers and local business.